GERAKAN KEAGAMAAN BARU DALAM INDONESIA KONTEMPORER: Tafsir Sosial Atas Hizbut Tahrir - Syamsul Arifin (IAIN Ponorogo, 2014)
New various religious movements in Islam have emerged in several Muslim countries, including in Indonesia. Many consider them to be a blatant manifestation of radicalism and fundamentalism of Islam although their proponents reject such a label. One of the rising movements in Indonesia is Hizbut Tahrir Indonesia (HTI). Fundamentalism is a common and widespread religious phenomenon since it is found trans-nationally. HTI represents the form of trans-national Islamic movement. This article seeks to examine HTI as a new rising trans-Islamic movement in contemporary Indonesia. By focusing on the HTI’s religious outlooks, ideology and social movement, this article argues that HTI is representation of fundamentalist movement. Fundamentalism here is defined as a form of religious movement that attempts to preserve fundamental tenets laid down in the Scripture, and reinterprets them in contemporary socio-political realms. The feature of fundamentalism in HTI is expressed in its religious thoughts and understanding and in the ways in which it re-appropriates Islamic doctrines in modern and contemporary socio-political contexts. Keywords: Hizbut Tahrir, fundamentalism, religious movements